E-Modul Pencemaran Mikroplastik Berbasis PBL: Upaya Meningkatkan Keterampilan Pemecahan Masalah Lingkungan Kontekstual pada Siswa: (PBL-Based E-Module on Microplastic Pollution: An Effort to Improve Students Contextual Environmental Problem-Solving Skills) - Syarif, Eka Aghnia; Saparuddin, Saparuddin; Putri, Husmayani Muny (BIODIK, 2025)
This study aims to examine the effectiveness of a Problem-Based Learning (PBL)-based e-module on microplastic pollution in the Sengguruh Reservoir in improving students’ problem-solving skills. This research employed a quasi-experimental design involving two classes selected through purposive sampling. The experimental class was taught using the e-module integrated with the PBL model, while the control class used a conventional textbook and direct instruction model. The results revealed that the use of the PBL-based e-module on microplastic pollution in the Sengguruh Reservoir was more effective in enhancing students’ problem-solving skills compared to traditional teaching methods. Therefore, the PBL-based e-module on microplastic pollution can serve as an effective alternative learning media to foster students' problem-solving skills in biology education. Key words: e-module, Problem-Solving Skills, Problem-Based Learning (PBL), Microplastic Pollution